Bullying Behavior among College Students in the Nusa Cendana University - Try Wahyulyangkara Debora Taunu; Dian Lestari Anakaka; R. Pasifikus Christa Wijaya (Universitas Nusa Cendana, 2021)
Bullying is a phenomenon that still occurs in the education world, including in higher education institution. The research objective was to identify the bullying behavior and the types of bullying and how it felt by students at Nusa Cendana University. This type of research uses quantitative research with the Man-Whitney U analysis design. The number of samples is 335 students from the University of Nusa Cendana. The results showed that the bullies are mostly coming from students aged 22-24 years old and students aged 18-19 years old are more often bullied. Male students were more likely to be bullied and be victims of bullying than female. Students who were on the committee during the student orientation period do have a higher physical bullying rate than those who have never been on the committee, raising some questions for the evaluation of the student orientation implementation. If the level of bullying experienced by students increases, the higher the level of bullying they do, thus prolonging the cycle of bullying in students.